2017
DOI: 10.1016/j.clim.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Cell death in the pathogenesis of systemic lupus erythematosus and lupus nephritis

Abstract: Nephritis is one of the most severe complications of systemic lupus erythematosus (SLE). One key characteristic of lupus nephritis (LN) is the deposition of immune complexes containing nucleic acids and/or proteins binding to nucleic acids and autoantibodies recognizing these molecules. A variety of cell death processes are implicated in the generation and externalization of modified nuclear autoantigens and in the development of LN. Among these processes, apoptosis, primary and secondary necrosis, NETosis, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
140
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(149 citation statements)
references
References 274 publications
(334 reference statements)
2
140
1
6
Order By: Relevance
“…Programmed cell death (PCD) culminates with efficient removal of cell corpses by tissue-resident macrophages coupled with the delivery of robust anti-inflammatory signals 148,149 . Conversely, RCD occurring in the context of failing adaptation to stress can be linked to the release of cellular content, including various pro-inflammatory signals 150 . The pro-inflammatory effects of RCD can underlie pathogenic maladaptation, as in the case of systemic lupus erythematosus (SLE) 150 .…”
Section: Exosomesmentioning
confidence: 99%
“…Programmed cell death (PCD) culminates with efficient removal of cell corpses by tissue-resident macrophages coupled with the delivery of robust anti-inflammatory signals 148,149 . Conversely, RCD occurring in the context of failing adaptation to stress can be linked to the release of cellular content, including various pro-inflammatory signals 150 . The pro-inflammatory effects of RCD can underlie pathogenic maladaptation, as in the case of systemic lupus erythematosus (SLE) 150 .…”
Section: Exosomesmentioning
confidence: 99%
“…53,54 In addition, monocyte chemoattractant protein (MCP-1) is implicated in the activation of inflammatory cells and has been suggested to affect the progression of lupus nephritis (LN). 55,56 Macrophages are the main origin of these inflammatory cytokines in SLE. In the current study, our in vivo and in vitro studies showed that ARA290 ameliorated inflammatory response in SLE mice and, notably, suppressed the expression of TNF-a, IL-6, iNOS and MCP-1 in macrophages, which suggested that ARA290 might alleviated the symptoms of SLE via regulating macrophage inflammatory response; however, the definite mechanism between ARA290 and macrophage inflammatory response needs further investigation.…”
Section: During Sle Treatmentmentioning
confidence: 99%
“…However, while the underlying mechanisms have not been fully elucidated, an increase in anti-MOG antibody is observed under these circumstances [90]. Hence, impaired apoptosis also seems of significance in MS pathogenesis as it occurs for other systemic autoimmune diseases, such as systemic lupus erithematosus [91]. …”
Section: Evidence About the Role Of The Gas6/tam System In Multiplmentioning
confidence: 99%